Distinct roles for RSC and SWI/SNF chromatin remodelers in genomic excision repair - Bohm, Kaitlynne A.; Hodges, Amelia J.; Czaja, Wioletta; Selvam, Kathiresan; Smerdon, Michael J.; Mao, Peng; Wyrick, John J.

(untitled) (Genome Research, 2021)
Nucleosomes are a significant barrier to the repair of UV damage because they impede damage recognition by nucleotide excision repair (NER). The RSC and SWI/SNF chromatin remodelers function in cells to promote DNA access by moving or evicting nucleosomes, and both have been linked to NER in yeast. Here, we report genome-wide repair maps of UV-induced cyclobutane pyrimidine dimers (CPDs) in yeast cells lacking RSC or SWI/SNF activity. Our data indicate that SWI/SNF is not generally required for NER but instead promotes repair of CPD lesions at specific yeast genes. In contrast, mutation or depletion of RSC subunits causes a general defect in NER across the yeast genome. Our data indicate that RSC is required for repair not only in nucleosomal DNA but also in neighboring linker DNA and nucleosome-free regions (NFRs). Although depletion of the RSC catalytic subunit also affects base excision repair (BER) of N-methylpurine (NMP) lesions, RSC activity is less important for BER in linker DNA and NFRs. Furthermore, our data indicate that RSC plays a direct role in transcription-coupled NER (TC-NER) of transcribed DNA. These findings help to define the specific genomic and chromatin contexts in which each chromatin remodeler functions in DNA repair, and indicate that RSC plays a unique function in facilitating repair by both NER subpathways.